MANAJEMEN RISIKO PEMASARAN HASIL TANGKAPAN KELOMPOK USAHA BERSAMA PERIKANAN TANGKAP “TUNAS HARAPAN” DI KELURAHAN TAMA POLE KECAMATAN MUARA JAWA - Diyan Fakhreza; Said Abdussyahid; Eko Sugiharto (2339-1324, 2022)
This research focuses more on marketing risk management, the purpose of this research is to identify risk opportunities and determine risk management policies towards the marketing of production results in the